Comparison of Electron Density and Absorption Dose Values of Artificial Boluses as Tissue Substitutes - D. R. Putri; F. K. Hentihu; R. J. Stevenly; E. R. Putri (National Research and Innovation Agency, 2026)
According to the Skin Cancer Foundation (SCF), approximately 1.8 million new cases of Squamous Cell Carcinoma (SCC) were reported globally in 2023. Radiotherapy remains a common treatment modality for SCC. However, delivering the maximum dose directly to the skin surface is often impeded by the skin-sparing effect of high-energy photon and electron beams. To overcome this limitation, a bolus, a tissue-equivalent material, is applied to bring the dose closer to the surface. This study aims to evaluate the electron density values derived from CT images and the absorbed doses of boluses fabricated from three different materials: resin Lycal 1079 (a propylene glycol-based compound), silicone rubber (polydimethylsiloxane), and plasticine (a mixture of stearate salt and glycerin). Dosimetric measurements were conducted using 6 MV photon beams and 12 MeV electron beams. Image analysis was performed using ImageJ and Matlab softwares. The irradiation setup employed a Source-to-Surface Distance (SSD) of 100 cm and a 10 × 10 cm² field size. Relative Electron Density (RED) values obtained from ImageJ for the resin and silicone rubber boluses were 1.007 and 1.188, respectively, while Matlab yielded RED values of 1.094 for resin and 1.194 for silicone rubber. For the plasticine bolus, both software tools produced a consistent RED value of 1.101. The findings indicate that beam energy has a significant impact on the absorbed dose at various phantom depths. Furthermore, all bolus materials increased the absorbed dose compared to setups without a bolus. Among the three materials, the resin bolus exhibited the most favorable characteristics, with a RED value closely approximating that of breast and skin tissue, highlighting its potential as an effective and economical tissue-equivalent bolus for clinical radiotherapy applications.